COMPARISON OF POPULATION SURVEY OF MULTAN ABOUT CIGARETTE SMOKING WITH SURVEY OF ABBOTTABAD - Jaleel, Muhammad Asif; Nooreen, Rozina; Parveen, Abida; Farhana, Farhana; Nadeem, Nadeem; Hameed, Abdul (Journal of Ayub Medical College Abbottabad, 2002)
Background: There are different pollutions in the environment e.g. Water pollution, dust pollution, pollen pollution, noise pollution and smoking pollution. As smoking from different sources is a pollution and injurious to health therefore we decided to conduct epidemiological study of smoking in Multan. Methods: The study was carried out on 1100 subjects residing in different localities of Multan. A specifically designed questionnaire was filled and the responses computed. The results were then compared with similar survey conducted in Abbottabad and reported earlier. Results: Out of the study population 40.02% were found to be smoking different kinds of tobacco. Out of 442 smoking persons 36.66% are smoking for just company while 57.01% for anxiety and remaining for other reasons. 20-40 cigarettes of different brands per day are used by different occupation persons. The expenditure for cigarette smoking is in the range of Rs. 300-2000 per month. Among smoking persons 292 (66.06 %) complained of Nocturnal cough, 96 (21.72%) during day and 54 (12.22 %) at both time. 125 smokers (28.28 %) complained of sputum, while 43 subjects (9.73 %) complained of occasional or frequent blood stained sputum. 24 (5.43 %) smokers reported of symptoms or diagnosis of Ischeamic heart disease. 35 smokers (7.92 %) smoke during fasting of Holy Ramadan. 290 smokers (65.61 %) do not hesitate to smoke at public places